Peranan Pendidikan Kristiani Berbasis Muatan Lokal Oi Mel Oi Kil Di Maluku - Resa Dandirwalu (Peneliti.net, 2020)
The purpose of this is to see the extent of the role of Christian Education in the local wisdom of Oi Mel Oi Kil paper culture formed from the culture of the Basudara people from two villages so that it strongly reflects the cultural heritage of the ancestors of the Kokwary village and Wakpapapy, which was developed in the form of binding agreements and oaths. This writing qualitatively uses a descriptive approach to see the overall cultural and individual background in the Kokwary community and Wakpapapy. The results of this paper would like to show that in local wisdomculture Oi Mel Oi Kil's actually implies various teachings that are able to uphold the values ​​of brotherhood and foster a sense of harmony, love, and affection in life as a person who in the role of Christianity is taught to love one another and a willingness to sacrifice even though in culture it is done in the form of oaths and promises.